Análise do campo termo-higrométrico da cidade de Uberlândia - MG - Silva, Igor Antônio (2017)
This work aimed to investigate the occurrence of the heat island phenomenon and to analyze the behavior of the thermal and hygrometric variation of the city of Uberlândia-MG and its relationship with different elements of the urban landscape. For this purpose, a bibliographic review was carried out on the theme that enabled the choice of the best methodology for the execution of mobile transects in the East-West and North-South direction of the urban perimeter, in the winter and summer seasons, respectively. The meteorological data of the urban atmosphere obtained were organized, systematized and statistically associated to the type of land cover and use in the city. The analysis of the data showed a thermal variation superior to 4ºC between the center and the periphery of the city of Uberlândia in both analyzed stations. The relative humidity of the air presented abrupt variations along the transects, accompanying the inverse tendency of the temperature oscillation. The correlation of the thermal-hygrometric data of the transects with the elements of the urban landscape demonstrated a great influence of the surrounding vegetation in the reduction of the temperature and increase of the relative humidity of the air. Areas with higher indices of buildings showed a contrary tendency characterizing the urban heat island.